Casing Collapse and Salt Creeping for an Iraqi Oil Field: Implications for Mitigation - Al-Hasnawi, Ali N. Abed; Hosseinian, Armin; Faraj, Ali K.; Salih, Ameen K. (Journal of Petroleum Research and Studies, 2024)
Casing collapse is considered one of the costliest problems that occurs in the oil industry, and it happens when the stresses or loads exceed the casing collapse resistance or due to casing wear and corrosion or salt creeping. For X oil field, located in Iraq’s southern east, a casing collapse phenomenon has been exposed in four wells, including well X-1, and the salt creeping may be the main reason because the collapsed casing section is encountered by a salt formation that may be creeping under compression. In this paper, Lower-Fars’s formation had been specified as the high-pressure salt formation that causes this problem according to the analysis of the provided data that included the depths of the collapse, log data and the final geological report. A new suggested casing design had been suggested by using pore pressure, fracture pressure, and horizontal stresses that were estimated by interactive petrophysics software from the well log data. The proposed and current casing designs were Simulated using Landmark-stress check software, and the proposed casing design indicates changing the grade from (L-80, 47 ppf) to (N-80, 53 ppf), which prevents the problem from recurring when drilling new wells in the same field as well as the proposed casing design can be economically considered feasible.